SISTEM MANAJEMEN KESELAMATAN DAN KESEHATAN KERJA PADA PROYEK PENINGKATAN STRUKTUR JALAN - Lokajaya, I Nyoman (Heuristic, 2017)
The purpose of this study was (1) Knowing the implementation of the management system of health and safety work on the project Improvement of Structure Road City Limits Muara Teweh - Kandui, (2) Determine the state of completeness of facilities related to the implementation of health and safety system working on the project, (3) Obtain great need for the cost of providing health and safety at work on the project. After the analysis of occupational health and safety system, it was found that (1) Implementation of occupational health and safety management in occupational health and safety system in a very good condition. It was manifested in the form of the performance of the application of the implementation of health and safety at work based on the Minister of Public Works No. 9 of 2008 with a value of 86.22%, (2) Completed facility related to the implementation of the system of occupational health and safety was average, which was shown from the results Assessment Completed amenities occupational safety and health based on the Minister of Public Works No. 9 of 2008 with a value of 76.36%, (3) of the need for the cost of providing health and safety based on the Minister of Public Works No. 9 in 2008 was Rp 169.37 million.Keywords:health and safety management system, project